ANALISIS BIAYA MARKETING MIX KAITANNYA DENGAN PENINGKATAN VOLUME PENJUALAN KOMPUTER PADA UD. GENIUS COMPUTER DENPASAR - Muji rotun; Putu Mela Ratini (Forum Manajemen, 2017)
marketing mix is one of marketing stragegy that very important and have effect toward improvement of selling volume. This study aim to find out to analyze the effect of marketing mix toward improvement of computer selling volume at UD. Genius Computer Denpasar in period of 2014-2015 partially and simultaneously, and to find out improvementof cost variable of marketing mix that have dominant effect to influence of improvement of computer selling volume. The result of classic assumption at normality test data has been clasiffied normal, multikoliniarity test is no multicolinierity, autocorrelation test of Durbin Watson = 1,924 it reside at between 1,55-2,46 there is no autocorrelation, heteroscedascity test is no heteroscedasity. The result of multiple regression analysis, cost of marketing mix partially have positive significant toward volume of computer selling. Analysis of F test shows marketing mix have significant effect simultaneously toward improvement of computer selling volume, the result of multiple linear regression of distribution cost value is dominant variable that have effect on improvement of computer selling volume